Contingent Work: American Employment Relations in Transition - Zeytinoglu, Isik Urla (Relations industrielles / Industrial Relations, 2000)
Contingent Work: American Employment Relations in Transition, edited by Kathleen Barker and Kathleen Christensen, is reviewed.
Keywords: Alternative work arrangements; Book reviews; Business And Economics–Labor And Industrial Relations; Business And Economics–Personnel Management; Employment; Labor Unions; Labor relations; SnR_publicationTitle_Relations Industrielles_Relations industrielles / Industrial Relations_2025-09-22T16:07:02.081Z; Temporary employment; Transitions